2022
DOI: 10.3389/fendo.2022.882163
|View full text |Cite
|
Sign up to set email alerts
|

Level-Specific Volumetric BMD Threshold Values for the Prediction of Incident Vertebral Fractures Using Opportunistic QCT: A Case-Control Study

Abstract: PurposeTo establish and evaluate the diagnostic accuracy of volumetric bone mineral density (vBMD) threshold values at different spinal levels, derived from opportunistic quantitative computed tomography (QCT), for the prediction of incident vertebral fractures (VF).Materials and MethodsIn this case-control study, 35 incident VF cases (23 women, 12 men; mean age: 67 years) and 70 sex- and age-matched controls were included, based on routine multi detector CT (MDCT) scans of the thoracolumbar spine. Trabecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 44 publications
3
20
0
3
Order By: Relevance
“…When the L3 vertebra could not be used due to fractures, hemangioma or other issues, the next lower possible vertebra was used for measurements. HU were than transformed to bone mineral density (BMD) by asynchronous calibration based on scanner specific equations [ 23 ]. We then used the cut-off values proposed by the American College of Radiology to define osteoporosis (BMD < 80.0 mg/cm 3 ) and osteopenia ≥ 80.0 to < 120.0 mg/cm 3 ) [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…When the L3 vertebra could not be used due to fractures, hemangioma or other issues, the next lower possible vertebra was used for measurements. HU were than transformed to bone mineral density (BMD) by asynchronous calibration based on scanner specific equations [ 23 ]. We then used the cut-off values proposed by the American College of Radiology to define osteoporosis (BMD < 80.0 mg/cm 3 ) and osteopenia ≥ 80.0 to < 120.0 mg/cm 3 ) [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…23 They found that automated opportunistic osteoporosis screening of vBMD along the entire thoracolumbar spine allows for risk assessment of imminent vertebral fracture and proposed a level-specific vBMD threshold at the thoracolumbar spine to identify individuals at high fracture risk. 23…”
Section: Opportunistic Computed Tomography Detection Of Osteoporosismentioning
confidence: 99%
“…23 They found that automated opportunistic osteoporosis screening of vBMD along the entire thoracolumbar spine allows for risk assessment of imminent vertebral fracture and proposed a level-specific vBMD threshold at the thoracolumbar spine to identify individuals at high fracture risk. 23 Internal calibration, also called patient-specific phantomless calibration, uses the patient's own internal tissues as a calibrating reference material. 24 Internal density calibration uses in-scan ROIs to determine a voxel-specific density calibration.…”
Section: Opportunistic Quantitative Computed Tomography and Asynchron...mentioning
confidence: 99%
“…Segmentation is not necessary in an automated pipeline. Adapted from Dieckmeyer et al [ 47 ] and Ibrahim et al [ 48 ].…”
Section: Figmentioning
confidence: 99%